A visual basic spreadsheet macro for recession curve analysis - Posavec, Kristijan (Ground water, 2006)
A Visual Basic program for an Excel spreadsheet was written to construct a master recession curve (MRC), using the adapted matching strip method, for recession analysis of ground water level time series. The program uses five different linear/nonlinear regression models to adjust individual recession segments to their proper positions in the MRC. The program can also be used to analyze the recession segments of other time series, such as daily stream discharge or stage. Some examples of field data from Croatia are used to illustrate the usefulness of its application